2010
DOI: 10.1051/0004-6361/201014295
|View full text |Cite
|
Sign up to set email alerts
|

Massive star formation in Wolf-Rayet galaxies

Abstract: Aims. We performed a comprehensive analysis of a sample of 20 starburst galaxies that show a substantial population of very young massive stars, most of them classified as Wolf-Rayet galaxies. Methods. In this paper, the last in the series, we analyze the global properties of our galaxy sample using multiwavelength data extracted from our own observations (Hα fluxes, B and H-band magnitudes) and from the literature, which include X-ray, FUV, FIR, and radio (both H i spectral line and 1.4 GHz radio-continuum) m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 279 publications
(264 reference statements)
3
52
0
Order By: Relevance
“…Various studies have addressed this aspect in BCDs (Chiosi 1979;Chiosi & Caimmi 1979;Maeder 1981Maeder , 1983Maeder , 1992Maeder , 1993Chiosi & Maeder 1986;Heger & Woosley 2002;López-Sánchez & Esteban 2009, 2010Zhao et al 2013). The α elements-to-oxygen abundance ratios in two star forming regions in Mrk 22 do not show any significant trends with observed metallicity, in agreement with results presented in Izotov et al (2006).…”
Section: Star Formation and Abundancesmentioning
confidence: 99%
“…Various studies have addressed this aspect in BCDs (Chiosi 1979;Chiosi & Caimmi 1979;Maeder 1981Maeder , 1983Maeder , 1992Maeder , 1993Chiosi & Maeder 1986;Heger & Woosley 2002;López-Sánchez & Esteban 2009, 2010Zhao et al 2013). The α elements-to-oxygen abundance ratios in two star forming regions in Mrk 22 do not show any significant trends with observed metallicity, in agreement with results presented in Izotov et al (2006).…”
Section: Star Formation and Abundancesmentioning
confidence: 99%
“…The degree of symmetry of a velocity field may also be affected by the presence of dust lanes, spiral arms, bars, warps, outflows/inflows, shocks or nuclear activity, minor mergers or even interactions with difuse objects (see, e.g., Fridman et al 2005;Fathi et al 2005;Wong et al 2004;López-Sánchez 2010). Their kinematics imprints could range from ∼10 km s −1 (see Wong et al 2004, for radial inflows) to a few hundred of km s −1 (for outflows from an AGN, see, e.g., Arribas et al 1996).…”
Section: Kinematic Internal Misalignmentmentioning
confidence: 99%
“…In the case of dwarf galaxies it has been suggested that interactions are responsible for the class of blue compact dwarfs (BCDs; Paudel et al 2015): dwarf galaxies with a significant, centrally concentrated young stellar population (e.g., Gil de Paz et al 2003). In general many dwarf systems with increased star formation rates (SFR) have been found to be irregular or to show signs of disturbances (Taylor et al 1995;Ekta & Chengalur 2010;López-Sánchez 2010;Holwerda et al 2013;Lelli et al 2014b;Knapen & Cisternas 2015), but in a number of cases no visible companion has been found (Brosch et al 2004;Ekta & Chengalur 2010;López-Sánchez 2010;Lelli et al 2014b). Other possible origins of the increase in star formation and the irregular morphology are cosmological gas inflows (see for example Verbeke et al 2014) or re-accretion of material blown out by previous starbursts, and varying internal instabilities (e.g., Meurer et al 1998;van Zee et al 2001;Lelli et al 2014a;Elmegreen et al 2012;Bekki & Freeman 2002).…”
Section: Introductionmentioning
confidence: 99%